Pregnant women with coronavirus disease 2019 and intrauterine vertical transmission: a systematic review - Arroyo-Sánchez, Abel Salvador (2020)
Introduction: Coronavirus disease 2019, also called COVID-19, is a potentially severe respiratory disease originated by the type 2 coronavirus that causes severe acute respiratory syndrome (SARS-CoV-2). Intrauterine transmission from mother to fetus is a matter of debate. Objective: To identify the available evidence of vertical intrauterine transmission in pregnant women with COVID-19. Methodology: A systematic review was performed using the terms: "Vertical transmission" AND "COVID-19" OR "SARSCoV-2" NOT "Review *". The databases consulted were MEDLINE/PubMed, Science Direct, Clinical Key, LILACS, SciELO, Google Scholar, medRxiv and SciELO Preprints. Results: Thirty primary studies met the selection criteria and included 476 pregnant women. Infection was found in 9 neonates (1.9%) in whom pharyngeal swabs were done within 48 hours of birth. In four of them the presence of the virus was not looked for in other maternal tissues and fluids; in the remaining 5 cases, the virus RNA was identified in the placenta of three of them, in two it was found in the amniotic fluid and in one in vaginal secretion. Studies were very heterogeneous, with great variety of the reported population, the number of samples and time of collection in neonates, the lack of sampling in maternal tissues and fluids. Conclusions: Vertical intrauterine transmission of SARS-CoV-2 has not been conclusively demonstrated in pregnant women with COVID-19 as the majority of patients with the disease had newborns with negative molecular test (98,1%). The heterogeneity of the studies does not allow to rule out this possibility either.